New Ancol Logo Design, Brings the Meaning of “Happiness” or “Disappointment” for Indonesian People - Edy Chandra; Maitri Widya Mutiara (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2022)
Discussing the brand of a company, of course, it will begin with a face called a logo. Ancol as one of the companies that focuses on local Indonesian tourism has taken a stand to change its image to the community. With one of his efforts to change the visual appearance of the Ancol logo with a new design. Unfortunately, the results of the hard work of Ancol Public Relations failed to win sympathy from the community. Some people expressed their dislike through a response on twitter. It turned out that the impact of the visual change actually received a negative response from most Indonesians who had had experience visiting Ancol before. This is a formulation of a problem that questions how the picture of the negative response of the Indonesian people to the visualization of the new Ancol Logo and the development efforts of Ancol public relations. Through a qualitative research method approach with the form of case studies that are explored through various mass media reports and progress on existing social media. In the discussion, there was a fact of opinion from a practitioner who stated the discrepancy of the change in the use of the originally colored to monotonous shades of blue. The next hope is that ancol public relations can listen and further develop the Ancol logo to a better form.